Advances in Enterprise Engineering XI : 7th Enterprise Engineering Working Conference, EEWC 2017, Antwerp, Belgium, May 8-12, 2017, Proceedings - Aveiro, David; Pergl, Robert (Springer International Publishing, 2017)
This book constitutes the proceedings of the 7th Enterprise Engineering Working Conference, EEWC 2017, held in Antwerp, Belgium, in May 2017. EEWC aims at addressing the challenges that modern and complex enterprises are facing in a rapidly changing world. The participants of the working conference share a belief that dealing with these challenges requires rigorous and scientific solutions, focusing on the design and engineering of enterprises. The goal of EEWC is to stimulate interaction between the different stakeholders, scientists as well as practitioners, interested in making Enterprise Engineering a reality. The 12 full papers and 4 short papers presented in this volume were carefully reviewed and selected from 40 submissions. They were organized in topical sections named: formalisms; standards and laws; business processes; normalized systems and evolvability; ontologies; and organization design.
International conference proceedings.
Includes author index.
Keywords: Systems engineering -- Congresses.; Management information systems -- Congresses.; elektronické knihy; electronic books